A Comprehensive Systematic Review of Comparative Effectiveness of Pharmacological and Lifestyle-Based Treatments for Painful Diabetic Peripheral Neuropathy - Pyarkatariana Putri Eka Pertiwi; Mayvita Muntadiroh (International Medical Journal Corp. Ltd, 2025)
Introduction: Painful diabetic peripheral neuropathy (PDPN) is a prevalent and debilitating complication of diabetes, characterized by chronic neuropathic pain that significantly impairs quality of life. The management landscape includes diverse pharmacological and lifestyle-based interventions, yet a comprehensive, comparative synthesis of their effectiveness, safety, and suitability across different patient contexts is needed. Methods: A systematic review was conducted. We screened sources based on predefined criteria including adult PDPN populations, and quantifiable pain outcomes. Data from 40 included sources were extracted on treatment comparisons, patient characteristics, effectiveness and safety outcomes, and study methodology. Results: Pharmacological treatments, particularly anticonvulsants (e.g., pregabalin, Level A evidence) and antidepressants (e.g., duloxetine, SNRIs), demonstrate robust efficacy, with combination therapies (e.g., pregabalin + lacosamide) showing superior response rates (80.6%) versus monotherapy (58.2%) (Muhamamd Riaz et al., 2025; S. Tesfaye et al., 2022). However, they are associated with significant side effects leading to dropouts. Conversely, lifestyle-based interventions like Transcutaneous Electrical Nerve Stimulation (TENS) showed equivalent efficacy to pregabalin with minimal adverse events (Metka Moharič et al., 2009). Psychological interventions (MBSR, CBT) yielded large, sustained effect sizes on pain and interference (Simona Racaru et al., 2020; H. Nathan et al., 2017). Direct comparisons revealed trade-offs; nortriptyline was more effective than TENS but had higher side-effect rates (Mehrnoosh Zakerkish et al., 2019). Discussion: The findings highlight that optimal treatment is not one-size-fits-all. Heterogeneity in outcomes is explained by treatment duration, baseline pain severity, and the superiority of multimodal approaches. Long-term durability favors behavioral and neuromodulation therapies, while pharmacological benefits may plateau. Safety profiles strongly favor non-pharmacological options. Conclusion: A personalized, stepped-care approach is recommended. For treatment-naïve patients with moderate pain, SNRIs or TENS are viable first-line options based on patient preference and comorbidities. Combination therapy is advised for partial responders. For refractory cases, interventional therapies like spinal cord stimulation may be considered. Future research should focus on long-term comparative trials and predictive biomarkers for treatment response.